2015
DOI: 10.1073/pnas.1423900112
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mechanistically distinct inhibitors of HIV-1 reverse transcriptase through fragment screening

Abstract: Fragment-based screening methods can be used to discover novel active site or allosteric inhibitors for therapeutic intervention. Using saturation transfer difference (STD) NMR and in vitro activity assays, we have identified fragment-sized inhibitors of HIV-1 reverse transcriptase (RT) with distinct chemical scaffolds and mechanisms compared to nonnucleoside RT inhibitors (NNRTIs) and nucleoside/ nucleotide RT inhibitors (NRTIs). Three compounds were found to inhibit RNA-and DNA-dependent DNA polymerase activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Although rare, inhibitory activities like these by low molecular weight fragments are not without precedent; La et al identified fragments that inhibited HIV reverse transcriptase with IC 50 values of 20–100 μM. 46 The low IC 50 values could also reflect potential assay interference. Fragment 21 has previously been identified as a frequent hitter, and as such is unlikely to prove a good lead for the development of inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Although rare, inhibitory activities like these by low molecular weight fragments are not without precedent; La et al identified fragments that inhibited HIV reverse transcriptase with IC 50 values of 20–100 μM. 46 The low IC 50 values could also reflect potential assay interference. Fragment 21 has previously been identified as a frequent hitter, and as such is unlikely to prove a good lead for the development of inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…In the most recently reported FBDD approach targeting HIV-1 RT, the Tachedjian group in Melbourne, Australia [100] used STD-NMR to screen a library of 630 fragments against HIV-1 RT to search for allosteric inhibitors at sites other than the NNIBP. STD-NMR was followed by a secondary screen using a HIV-1 RT polymerase activity assay, where eight fragment hits were identified with micromolar potencies against the DNA polymerase function of wild-type (WT) HIV-1 RT.…”
Section: Fbdd Screening Against Hiv-1 Rt To Discover Novel Allostericmentioning
confidence: 99%
“…Only three of the hits, 8-10 (Table 3) maintained a similar potency against WT RT and three clinically relevant NNRTI-resistant RT mutants, K103N, Y181C and G190A. In contrast to Bauman et al [98], this group [100] then used biochemical assays to gather evidence about the mechanisms of action and possible binding sites on the enzyme for the top three fragment hits. Two of three fragments, 9 and 10, were shown to compete with the HIV-1 RT substrates, nucleotide and T/P, respectively, suggesting that these two compounds could be inhibiting the enzyme allosterically with fragment 9 likely acting at or near the polymerase active site, such as the NcRTI binding site [101] or another allosteric site.…”
Section: Fbdd Screening Against Hiv-1 Rt To Discover Novel Allostericmentioning
confidence: 99%
See 1 more Smart Citation
“…Existence of several shortcomings of the current ART, including the emergence of resistant virus, severe side effects and the high cost, has posed an urgent need for the discovery and development of potent anti-HIV-1 drugs with novel modes of action. 1 Marine organisms have been proven to be excellent sources of biologically active compounds against HIV-1. Discovery of anti-HIV-1agents, especially with novel modes of action, from marine organisms is becoming more attractive and promising.…”
Section: Introductionmentioning
confidence: 99%